Computational Study of Mammalian Alcohol Dehydrogenase 5 - The Odd Sibling - Östberg, Linus; Höög, Jan-Olov; Persson, Bengt (Karolinska Institutet, 2015)
Structure and sequence analysis of Alcohol Dehydrogenase 5.
Keywords: Medical and Health Sciences; Medicin och hälsovetenskap